1976
DOI: 10.3109/02844317609105199
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Z Plasty On Hypertrophic Scars

Abstract: Hypertrophic scar tissue has been observed to soften and thin following Z plasty without removal of any of the scar tissue. Histochemical studies of tissue before and after Z plasty showed that abnormally sulfated mucopolysaccharides were replaced by normal acid mucopolysaccahrides within 14 days. Collagen in hypertrophic scar appeared in nodules and fibers perpendicular to the surface of the skin rather than as long straight fibers parallel to the skin surface as normally seen. Elastic fibers were reduced and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The relatively low resting tension of murine skin also suggested that the intrinsic forces in murine skin might not be sufficient to activate the processes that lead to human hypertrophic scarring. This, in addition to extensive clinical evidence (3,7,10), served as the rationale for using an external tension device to augment the biomechanical forces on murine skin and replicate the forces normally experienced by human skin in a murine model.…”
Section: Differences In Biomechanical Properties Of Human and Mouse Smentioning
confidence: 99%
“…The relatively low resting tension of murine skin also suggested that the intrinsic forces in murine skin might not be sufficient to activate the processes that lead to human hypertrophic scarring. This, in addition to extensive clinical evidence (3,7,10), served as the rationale for using an external tension device to augment the biomechanical forces on murine skin and replicate the forces normally experienced by human skin in a murine model.…”
Section: Differences In Biomechanical Properties Of Human and Mouse Smentioning
confidence: 99%
“…1. Such damage can ultimately lead to tissue responses including inflammation, scarring and abnormal desquamation and further exacerbate the effects of skin disorders such as atopic dermatitis, ichthyosis vulgaris and chronic xerosis [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Such procedures, however, require a more invasive operation and do not improve the existing superficial meshed pattern. 26,27 The fractional CO 2 laser is a relatively new modality that attempts to break up the tension across a hypertrophic wound, incite collagen turnover, and allow for a more "normal" wound healing process to take place. 10,14-17 Similar to a Z-plasty, the laser breaks up the thick, disorganized collagen fibrils that created the scar, allowing these regions to reheal in a more organized fashion.…”
Section: Discussionmentioning
confidence: 99%
“…10,14-17 Similar to a Z-plasty, the laser breaks up the thick, disorganized collagen fibrils that created the scar, allowing these regions to reheal in a more organized fashion. 16,26,27 Objective assessment of scars is notoriously difficult, and existing scales, such as the Vancouver scar scale, are difficult to standardize. Furthermore, the time course for scar maturation is inconsistent and dependent on multiple known and unknown variables.…”
Section: Discussionmentioning
confidence: 99%